2020
DOI: 10.1101/2020.04.01.20050443
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can N95 respirators be reused after disinfection? And for how many times?

Abstract: The Coronavirus Disease 2019 pandemic has led to a major shortage of N95 respirators, which are essential to protecting healthcare professionals and the general public who may come into contact with the virus. Thus, it is essential to determine how we can reuse respirators and other personal protection in these urgent times. We investigated multiple commonly used and easily deployable, scalable disinfection schemes on media with particle filtration efficiency of 95%. Among these, heating (≤85 °C) under variou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
194
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(207 citation statements)
references
References 32 publications
4
194
0
9
Order By: Relevance
“…• While two studies have looked at the effects of 3 heat treatment cycles for 15 minutes 38 and 30 minutes 40 at 60°C on N95 FFRs, no peer-reviewed studies seem to have looked at the potential effects of more than 3 heat treatment cycles or multiple cycles of longer duration on N95 FFRs. The exception is Liao et al (2020) 41 , who have recently reported that 20 cycles of dry heat at 75°C for 30 minutes did not affect the filtration efficacy of the key fabric in N95 FFRs. However, due to their methodology it was not possible to ascertain whether the fit of the masks for example, would be affected by their treatment protocol.…”
Section: Heat Treatmentmentioning
confidence: 97%
See 2 more Smart Citations
“…• While two studies have looked at the effects of 3 heat treatment cycles for 15 minutes 38 and 30 minutes 40 at 60°C on N95 FFRs, no peer-reviewed studies seem to have looked at the potential effects of more than 3 heat treatment cycles or multiple cycles of longer duration on N95 FFRs. The exception is Liao et al (2020) 41 , who have recently reported that 20 cycles of dry heat at 75°C for 30 minutes did not affect the filtration efficacy of the key fabric in N95 FFRs. However, due to their methodology it was not possible to ascertain whether the fit of the masks for example, would be affected by their treatment protocol.…”
Section: Heat Treatmentmentioning
confidence: 97%
“…• Based on the available evidence, there are uncertainties about using our recommended heat treatment at 60°C for 90 minutes for N95 FFRs, as the extended time required for heat treatment may have adverse effects that could compromise its safety for reuse, especially after multiple disinfection cycles. However, a recent report by Liao et al 41 suggests that our proposed heat treatment regimen could be applied to N95 FFRs, and could therefore be adopted in the absence of UVC treatment.…”
Section: Summary On the Impact Of Disinfection On N95 Ffrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a group at Stanford University and 4C Air, Inc. (Sunnyvale, CA), led by Stanford professor of materials science and engineering Yi Cui, has experimented with baking [6,7]. Their current standard is to bake the masks at 75 °C for 30 min.…”
Section: Baking and Comparisonsmentioning
confidence: 99%
“…Microwaving, for example, can partially melt the masks [5]. Alcohol and bleach destroy the static charge within the mask, which is vital to its proper function [5,6]. The active layer of an N95 mask is 90% empty space, so the fibers need help to trap 95% of the particles that pass through-they get that help from static electricity [6,7].…”
mentioning
confidence: 99%